Arterial spin labeling signal ratio between the lesion and contralateral sides for evaluation of acute middle cerebral artery infarct. Issue 2 (14th January 2022) - Lee, Junyoung; Park, Dong Woo; Kim, Young Seo; Kim, Hyun Young; Lee, Young-Jun
Abstract : Abstract: The purpose of our study was to differentiate arterial transit artifact from post-recanalization luxury perfusion on arterial spin labeling (ASL) image, and obtain the relationship between ASL signal intensity and clinical outcomes in patients with acute ischemic stroke. Thirty-five subjects with an acute middle cerebral artery (MCA) infarct were enrolled (18 with recanalized and 17 with non-recanalized MCAs). ASL images were obtained using pseudo-continuous ASL technique with 1600 ms (millisecond) of post-label delay within 3 days from symptom onset. Signal intensities on color ASL images were classified as high, intermediate, and poor grade visually. The ratio of maximum ASL signal between the ischemic area and contralateral side was calculated and compared between patients with and without MCA recanalization. Among patients with non-recanalized MCA, ASL signal ratios were compared between patients with and without hyperintense vessel sign on fluid attenuated inversion recovery (FLAIR). Also, correlation between the ASL signal ratio and National Institutes of Health Stroke Scale (NIHSS) score was evaluated. High or intermediate grade on color ASL images were more frequently found in patients with recanalized MCA ( P < .01). Patients with non-recanalized MCA had higher ASL signal ratio in overall ASL signal grade ( P = .010) and intermediate grade ( P = .011). Among patients with non-recanalized MCA, those with hyperintense vessel sign on FLAIR had higher ASL signal ratios ( P = .049). ASL signal ratio was negatively correlated with both initial ( P = .023) and final ( P = .003) NIHSS scores. The ASL signal ratio could help to differentiate between the pial collaterals and post-recanalization luxury perfusion. A higher ASL ratio was related with the hyperintense vessel sign on FLAIR and lower NIHSS score.